Establishment and application of an RNAi system in Pichia pastoris - Ruan, Shupeng; He, Chenfeng; Wang, Aoxue; Lin, Ying; Liang, Shuli (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionReducing endogenous gene expression is key in microbial metabolic engineering. Traditional methods for gene knockout or suppression can be slow and complex. RNA interference (RNAi) provides a faster way to regulate gene expression using plasmids with hairpin RNA. This study examines single- and double-gene suppression in P. pastoris, a common system for expressing heterologous proteins. We also use reporter strains displaying EGFP on the cell surface to identify factors affecting protein secretion.MethodsWe established an RNAi system in P. pastoris by introducing plasmids containing hairpin RNA targeting specific genes. Reporter strains expressing EGFP on the cell surface were used to monitor the impact of gene suppression on protein secretion. Genes such as YAP1, YPS1, PRB1, and PEP4 were targeted for RNAi. Additionally, RNAi was applied to inhibit fatty acid synthesis to improve the conversion of malonyl-CoA to 3-hydroxypropionate (3-HP).ResultsSuppressing YAP1 and YPS1 reduced EGFP display by 83% and 48.8%, respectively. In contrast, suppressing PRB1 and PEP4 increased EGFP display by 33.8% and 26.5%, respectively. These findings show that regulating endogenous genes can significantly impact protein secretion in P. pastoris. Furthermore, RNAi inhibition of fatty acid synthesis improved 3-HP production.DiscussionThis study demonstrates the successful establishment of an RNAi system in P. pastoris, enabling efficient gene suppression for metabolic engineering. RNAi offers a faster and more efficient method for regulating gene expression, improving heterologous protein secretion and 3-HP production. This system is a valuable tool for optimizing P. pastoris as a microbial cell factory, with strong potential for industrial applications.